2016
DOI: 10.1561/104.00000038
|View full text |Cite
|
Sign up to set email alerts
|

No More Weekend Effect

Abstract: Before 1975, the mean weekend rate of return on the equal-weight (value-weight) stock market portfolio is significant −18bp (−19bp). After 1975, it is insignificant −5bp (−1bp). This break date is determined by a structural break test with unknown break date. The weekend effect is no longer an anomaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
4
8
0
Order By: Relevance
“…The purpose of this study is to contribute some new empirical evidences on the weekend effect for the industry-style portfolios in the US stock market using data over 90 years.Design/methodology/approach -The authors re-examine persistence or reversal of the weekend effect in the industry portfolios consisting of The New York Stock Exchange (NYSE), The American Stock Exchange (AMEX) and The National Association of Securities Dealers Automated Quotations exchange (NASDAQ) stocks using daily returns from 1926 to 2017. Our results confirm varying dates for structural breaks across industrial portfolios.Findings -As for the existence of weekend effects, the authors get mixed results for different portfolios.However, the overall findings provide broad support for the absence of weekend effects in most of the industrial portfolios as reported in Robins and Smith (2016). In addition, structural breaks for other weekdays and days of the week effects for other days have also been documented in the paper.Originality/value -As far as the authors are aware, this paper is the first research that analyzes weekend effect for the industry-style portfolios in the US stock market using data over 90 years.…”
supporting
confidence: 73%
See 3 more Smart Citations
“…The purpose of this study is to contribute some new empirical evidences on the weekend effect for the industry-style portfolios in the US stock market using data over 90 years.Design/methodology/approach -The authors re-examine persistence or reversal of the weekend effect in the industry portfolios consisting of The New York Stock Exchange (NYSE), The American Stock Exchange (AMEX) and The National Association of Securities Dealers Automated Quotations exchange (NASDAQ) stocks using daily returns from 1926 to 2017. Our results confirm varying dates for structural breaks across industrial portfolios.Findings -As for the existence of weekend effects, the authors get mixed results for different portfolios.However, the overall findings provide broad support for the absence of weekend effects in most of the industrial portfolios as reported in Robins and Smith (2016). In addition, structural breaks for other weekdays and days of the week effects for other days have also been documented in the paper.Originality/value -As far as the authors are aware, this paper is the first research that analyzes weekend effect for the industry-style portfolios in the US stock market using data over 90 years.…”
supporting
confidence: 73%
“…However, we believe that the results and findings in this paper have the potential to be generalized and applied to other types of portfolios and markets. This is especially true since Robins and Smith (2016) have already reported similar results in the context of the broader market.…”
Section: Datasupporting
confidence: 53%
See 2 more Smart Citations
“…The weekend effect has not existed since 1975 (Robins and Smith, 2016). The presence of a strong cross-sectional effect is still not surprising since mood variations provide clear predictions, but these patterns do not lead to comprehensive predictions.…”
Section: Introductionmentioning
confidence: 98%